Primary cilium depletion typifies cutaneous melanoma in situ and malignant melanoma. - Jinah Kim (Public Library of Science (PLoS), 2011)
Cutaneous melanoma is a lethal malignancy that arises spontaneously or via in situ precursor neoplasms. While melanoma in situ and locally invasive malignant melanoma can be cured surgically, these lesions can sometimes be difficult to distinguish from melanocytic nevi. Thus, the identification of histolopathologic or molecular features that distinguish these biologically distinct lesions would represent an important advance. To this end, we determined the abundance of melanocytic primary cilia in a series of 62 cases composed of typical cutaneous melanocytic nevi, melanoma in situ, invasive melanoma, and metastatic melanoma. Primary cilia are sensory organelles that modulate developmental and adaptive signaling and notably, are substantially depleted from the neoplastic epithelium of pancreatic carcinoma at a stage equivalent to melanoma in situ. In this series, we find that while nearly all melanocytes in 22 melanocytic nevi possessed a primary cilium, a near-complete loss of this organelle was observed in 16 cases of melanoma in situ, in 16 unequivocal primary invasive melanomas, and in 8 metastatic tumors, each associated with a cutaneous primary lesion. These findings suggest that the primary cilium may be used to segregate cutaneous invasive melanoma and melanoma in situ from melanocytic nevi. Moreover, they place the loss of an organelle known to regulate oncogenic signaling at an early stage of melanoma development.